LEGAL AND ECONOMIC ASPECTS FOR IMPLEMENTATION OF NATIONAL FUND ON CLIMATE CHANGE IN BRAZIL - Lanzillo, Anderson; Guimarães, Patricia Borba Vilar (Revista Direito E-nergia, 2014)
LEGAL AND ECONOMIC ASPECTS FOR IMPLEMENTATION OF NATIONAL FUND ON CLIMATE CHANGE IN BRAZIL